Prediksi Financial Distress Dengan Menggunakan Bankruptcy Prediction Model - Eka Zahra Solikahan; Nurhayati Olii (Al-Buhuts, 2022)
This study aims to determine financial distress by using the Bankruptcy Prediction Model Altman Z-Score and to validate the Altman Z-Score variable in the telecommunications sub-sector listed on the Indonesia Stock Exchange. A quantitative approach with bankruptcy prediction model Altman Z-score and correlation analysis using Eviews is used in this study. The results show that during the 2015-2019 observation period, the telecommunications sub-sector companies as a whole experienced financial distress, but in 2017 the category was healthy. In addition, the results of the research based on the telecommunication sub-sector companies obtained were Telekomunikasi Indonesia Tbk (TLKM) in healthy condition, Bakrie Telecom Tbk (BTEL) and Smartfren Telecom Tbk (FREN) in financial distress, XL Axiata Tbk (EXCL) and Indosat Tbk (ISAT), gray area condition. The results of the correlation ratio of the Altman Z-Score variable obtained the strongest correlation, namely the ratio variable X2, X3 and X5, the ratio variable X1, the category is quite strong and the one that gives the smallest contribution is X4 with the low category. The results of this study are expected to contribute to knowledge about the potential for financial distress with the bankruptcy prediction model in order to minimize the risk of bankruptcy,